Application of the AP4M Model Reading Skills Students at Tanah Ombak Padang Reading Park - Gusnetti (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The application of the AP4M model of reading skills was carried out in the Tanah Ombak reading park based on observations and interviews with the culture and learning methods of the Minangkabaau Natural School students as well as students in the Tanah Ombak reading park. The purpose of the study was to describe the reading ability of the Tanah Ombak Reading Community students. The theory used is the theory by Akaaya (2012), Haromi (2014), and Akin (2014). The methods used in this research are qualitative and quantitative methods. The research subjects were 8 students at Tanah Ombak Reading Park which consisted of 3 students in grade 3, 6 students in grade 4, 4 students in grade 5 and 5 students in grade 6. The results of data analysis showed that the average score obtained by grade 3 students as much as 9.50, the average value obtained by grade 4 students is 8.15, the average value obtained by grade 5 students is 7.50, and the average value obtained by grade 6 students is 8.48. reading with the AP4M model, the students of Tanah Ombak Reading Park are able to read well with a score of 8.29 in the very good category